Representasi Kepahlawanan Founding Fathers Indonesia dalam Desain Mata Uang Rp 100.000 dari Masa ke Masa - Wulan Eka Handayani; Muhammad Duta Komarudin (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Banknotes function not only as instruments of economic exchange but also as symbolic media of communication between the state and its citizens, representing a nation’s social, cultural, and political conditions. The design of Indonesian Rupiah banknotes, particularly the Rp100,000 denomination, embodies visual representations of the heroism of Indonesia’s founding fathers that have evolved from 1999 to 2016. This study aims to analyze and interpret the meanings underlying changes in the visual representations of Soekarno and Mohammad Hatta as reflections of dominant national narratives. Employing a descriptive qualitative approach, the research applies Charles Sanders Peirce’s semiotic analysis through the concepts of representamen, object, and interpretant, as well as the classification of signs into icons, indices, and symbols. The data were analyzed through the identification of visual elements, interpretation of meanings, and comparative analysis across periods. The findings reveal a transformation in the meaning of heroism, shifting from an emphasis on political legitimacy and parliamentary democracy in the 1999 series, to historical authority and the moment of proclamation in the 2014 series, and ultimately to the reinforcement of cultural identity and national diversity in the 2016 series. These changes demonstrate that representations of heroism are dynamic and continuously reconstructed in accordance with the political, social, and cultural contexts of each period.